Measurement technology for process automation - Andersson, Anders (Metrologist) (CRC Press, 2017)
"Almost every industry that use liquids and gas in any form has a need to measure flow, temperature and pressure. This text is a practical guide on how to accurately use these measuring instruments to control processes in manufacturing industries for food, beverages, chemicals, pharmaceuticals, oil, water and waste water, power, etc. With higher prices of raw materials and more severe requirements for safety and environmental issues, there is a growing demand to measure with higher precision. The book includes a number of practical examples from various industries. It discusses how to comply with safety standards regarding measurements and explains how legal control systems apply to measurements. The aim is to help any process industry reduce the risk of high costs and damage to both people and equipment."--Provided by publisher